The National Electronic Library: a guide to the future for library managers, editado por Gary M. Pitkin - Cunha, Murilo Bastos da (Revista de Biblioteconomia de Brasília, 1997)
PITKIN, Gary M. (ed.). The National Electronic Library: a guide to the future for library managers. Westport: Greenwood Press, 1996. 192 p.